What Are Orthopaedic Healthcare Professionals' Attitudes Toward Addressing Patient Psychosocial Factors? A Mixed-Methods Investigation. Issue 2 (15th February 2022) - Reichman, Mira; Bakhshaie, Jafar; Grunberg, Victoria A.; Doorley, James D.; Vranceanu, Ana-Maria
Abstract: Background: Integrating psychosocial resources into orthopaedic clinics can reduce psychological distress and opioid use after injury, enhance functional outcomes, and increase patient satisfaction with care. Establishing referral pathways for connecting orthopaedic patients with psychosocial resources requires the active collaboration and buy-in of orthopaedic healthcare professionals. Designing and disseminating psychosocial training materials for orthopaedic healthcare professionals requires a nuanced understanding of orthopaedic healthcare professionals' current attitudes toward addressing psychosocial factors, including any stigma and misconceptions about mental health that exist. Questions/purposes: (1) What are orthopaedic healthcare professionals' attitudes toward addressing patient psychosocial factors, and how are they related? (2) How do orthopaedic healthcare professionals' beliefs, reasonings, and experiences help to explain these attitudes? (3) How do attitudes differ between physicians and nonphysician healthcare professionals? Methods: In this multisite, mixed-methods study (that is, a study collecting both quantitative and qualitative data), our team of psychology researchers conducted qualitative focus groups over secure live video with 79 orthopaedic healthcare professionals at three geographically diverse Level I trauma centers. We approached all orthopaedic healthcare professionals within the three trauma centers to participate in the study to collect as many diverse perspectives as possible. Eighty-four percent (79 of 94) of the professionals we approached participated in qualitative data collection (the group of professionals comprised 20 attending surgeons; 28 residents; 10 nurse practitioners, registered nurses, and physician assistants; 13 medical assistants; five physical therapists and social workers; and three research fellows). We also asked participants to complete self-report items that assessed their attitudes toward addressing patients' psychosocial factors (research question 1). The different attitudes identified through the quantitative measurement served as a priori defined themes within which our two independent coders organized the qualitative data and identified beliefs and experiences that explained attitudes (research question 2). We used both quantitative and qualitative data to assess differences between surgeons and residents and nonphysician healthcare professionals (research question 3). Results: We quantitatively identified six underlying attitudes toward addressing psychosocial factors: professional confidence, perceived resource availability, fear of offending patients, fear of negative patient reactions, blame toward patients, and professional role resistance. We observed a strong quantitative correlation between the attitudes of professional confidence and perceived resource availability, and qualitative data revealed how healthcare professionals' willingness to discuss psychosocial issues with patients is shaped by their perception of psychosocial resources available for orthopaedic patients, as well as their perception of their own skills and tools to navigate these conversations. Quantitative data suggested that surgeons and residents endorse higher blame toward patients for psychosocial factors (medium effect size; p = 0.04), which is a stigmatizing attitude that serves as a barrier to integrating psychosocial resources into orthopaedic settings. Conclusion: The varying levels of confidence orthopaedic healthcare professionals reported with respect to the topic of discussing psychosocial factors and the misconceptions they endorse regarding psychosocial factors (such as blame toward patients) highlight the need for more specific education for orthopaedic healthcare professionals to help equip them with skills to raise and discuss psychosocial factors with patients in an empathic and destigmatizing manner. Clinical Relevance: The strong relationship observed between the attitudes of professional confidence and perceived resource availability suggests that expanding the provision of psychosocial resources in orthopaedic settings and establishing specific, efficient referral processes to connect patients with psychosocial resources will in turn increase orthopaedic healthcare professionals' confidence discussing psychosocial issues with patients.